Cohort Study: Pregnant Exercise with Primigravida Stage II of Labor Delivery - Latifatul Kamilia; Ahmaniyah, Ahmaniyah; Ratna Indriyani; Emdat Suprayitno (International Journal of Health Engineering and Technology, 2024)
Pregnancy exercise is a program for healthy pregnant women to prepare for the mother's physical condition. Suppose the mother does not do pregnancy exercise. In that case, she will experience aches, get tired quickly during pregnancy, and her delivery is not smooth in the second stage, thereby increasing fetal distress. This study determined the relationship between pregnancy exercise and the duration of the second stage of labor in primigravida in the Ambunten Health Center Work Area. The study design used a cohort analytic using a retrospective approach. The population was all primigravida women giving birth from September 2019 to September 2021. The sample taken was 179 respondents using a non-probability sampling technique. The second stage of labor They were then analyzed using the chi-square test. The results obtained from 179 respondents who did pregnancy exercise during the second stage of labor (74%) and did not do pregnancy exercise were not smooth (9%). The data analysis obtained the results with a p-value (0.000) and an error rate of the p-value (0.05). Conclusion H0 is rejected, and H1 is accepted. This means that there is a relationship between pregnancy exercise and the duration of the second stage of labor in primigravida in the Ambunten Health Center Work Area. This study concludes that respondents who did pregnancy exercise experienced a smooth process of the second stage of labor. Thus, it is recommended that respondents be more active in carrying out pregnancy exercises and that health workers intensify pregnant women to participate in classes for pregnant women.